Decline of arterial cerebral infarction among young women: the Bergen Stroke Study - Naess H; Fromm; Iversen; Thomassen L; Waje-Andresassen U (Vascular Health and Risk Management, 2011)
Halvor Naess1, Annette Fromm1, Ole Erik Iversen2, Lars Thomassen1, Ulrike Waje-Andreassen11Department of Neurology, 2Department of Gynecology, Haukeland University Hospital, University of Bergen, NorwayObjective: To assess the frequency of females and males aged ≤30 years with cerebral infarction in two different time periods.Methods: All patients aged ≤30 years with arterial cerebral infarction in 1988–1997 and 2006–2010 admitted to Haukeland University Hospital in Bergen, Norway, were included. Risk factors and etiology were assessed.Results: Between 1988 and 1997, 16 females and 7 males had cerebral infarction, whereas 0 females and 13 males had cerebral infarction in 2006–2010 (P = 0.0001). The incidence of cerebral infarction in females was significantly lower between 2006 and 2010 than between 1988 and 1997 (P = 0.007).Conclusion: Our findings suggest that the frequency of cerebral infarction among young females has dropped significantly during recent years.Keywords: cerebral infarction, Hordaland County, young females, males